Selenium biofortification of green spinach with optimum phosphorus fertilization and selenium application timing - Nayan, Dayang Safinah; Zainol, Rozlaily; Abdul Sukor, Arina Shairah; Mohammad Yusoff, Martini; Ishak, Che Fauziah (Wiley, 2020)
A selenium (Se) biofortification program for vegetables has never been attempted in Malaysia. This study was performed to determine the optimum Se fertilization rates for high yield and Se uptake by green spinach (Amaranthus spp.) through a glasshouse experiment and to evaluate the effect of Se application timing on dry matter, growth, and Se accumulation in green spinach through field experiments. Glasshouse experiment conducted with factorial randomized complete block design showed that applying P fertilizer as recommended for green spinach increased yield and Se uptake by the leaves and stems of green spinach. Selenium application in the form of Se(IV) solution at 120 g ha–1 to sandy clay soil was determined to be the optimum application rate, as higher rates reduced plant yield and decreased Se uptake by green spinach. Three cycles of field experiments showed that a single application of 120 g ha–1 Se at 14 d after planting (DAP) produced the optimum results in terms of green spinach growth and dry matter. Although the highest Se accumulation in leaves was observed when Se was applied at 7 DAP (26.04–29.20 μg 10 plants–1), its detrimental effect on yield caused it to be considered an inappropriate time of application. Therefore, with optimum Se accumulation in leaves (21.16–22.38 μg 10 plants–1) and stems (5.89–5.98 μg 10 plants–1), application of Se as Se(IV) solution at 14 DAP at a rate of 120 g ha–1 has been identified as an effective Se fertilization management strategy for producing Se-biofortified green spinach.